Managing the emancipated curriculum in transformational senior high schools: A phenomenological study in West Lombok - Baiq Sri Herlina Muliati; Slamet Lestari (Jurnal Penelitian Ilmu Pendidikan, 2024)
Character-based education is increasingly important in the Society 5.0 era as globalization and digitalization challenge traditional values. Indonesia introduced the Emancipated Curriculum to address learning loss and strengthen the Pancasila Student Profile Project (P5), which emphasizes both intellectual and moral development. However, gaps remain between curriculum ideals and school-level implementation, particularly due to heavy teacher administrative burdens and limited supervision. This study examines how two Teacher Empowerment public senior high schools in West Lombok manage the Emancipated Curriculum through four management functions: planning, organizing, implementing, and supervising. A qualitative phenomenological approach was conducted at Senior High School 1 Gerung. Data were collected through in-depth interviews with school leaders, teachers, and supervisors, non-participant observations, and analysis of curriculum documents. Data validity was ensured using the Miles and Huberman interactive analysis model, along with triangulation and member checking. The findings show that curriculum planning was systematic and collaborative, producing context-based plans aligned with student needs. Curriculum organization was adaptive and participatory, supported by functional teams and regular coordination. Learning implementation shifted toward student-centered, differentiated, and project-based instruction that integrated character education and local community contexts. Supervision became more reflective through academic supervision, peer review, and digital reporting, although consistent follow-up remains a challenge. Effective curriculum management was marked by collaborative leadership, community involvement, and continuous teacher development.